Variation Of Native Arabic Speakers' Responses To The Question Kaifa Haluk On YouTube Media: A Sociolinguistic Study/ Variasi Jawaban Penutur Asli Arab terhadap Pertanyaan Kaifa Haluk Di Media YouTube: Kajian Sosiolinguistik - Lillahi Wahdah, Dainunah; Tamarisa Syarova, Ilvi; Tatang (Bumi Lingua Edu Center, 2024)
This study examines the variation in native Arabic speakers' responses to the question kaifa haluk/ كيف حالك (How are you?) in the context of communication on the YouTube platform, specifically through the Iday Adventurer channel. The study aims to describe the forms of responses given by native Arabic speakers and to analyze the social factors influencing language choices, such as the use of formal language (fusha) and everyday language (’amiyah dialect). Data were collected using the Video Content Analysis (VCA) technique, which involves converting spoken interactions in videos into text data for qualitative analysis. The findings show a range of responses tailored to social context and the relationships between speakers, generally influenced by factors such as age, educational background, and the closeness of social ties. This study concludes that digital communication, particularly on YouTube, reflects rich sociolinguistic dynamics, where native Arabic speakers adjust their language choices according to situational and social backgrounds. This research provides additional insight into Arabic language variation on social media and the role of social context in the use of informal and formal language in the digital realm.